Impacts of Rural Electrification Revisited – The African Context - Jörg Peters; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
The investment requirements to achieve the United Nations' universal electricity access goal by 2030 are estimated at 640 billion US Dollars. The assumption underlying this goal is that electrification contributes to poverty alleviation in many regards. In recent years, a body of literature has emerged that widely confirms this positive poverty impact assumption. Most of these studies, however, are based on data from Asia and Latin America. This paper challenges the transferability of impact findings in the literature to the African context. Using a unique data set that we collected in various African countries we show that impact expectations on income, education, and health should be discounted considerably for Africa, at least in the shorter run. In many cases, the low levels of electricity consumption can also be served by low-cost solar alternatives. To ensure cost-efficient usage of public investments into rural electrification, we call for careful cost-benefit comparisons of on-grid and off-grid solutions.
Keywords: O33; P46; Q41; 330; energy access; on-grid electrification; off-grid electrification; Africa